2016
DOI: 10.1089/lrb.2015.0010
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Education on Upper Extremity Function in Patients with Lymphedema after Breast Cancer Treatments

Abstract: This study underscores the need to develop and implement strategies for LE prevention and education for all breast cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…Eighteen ADL/IADL studies (31%) reported non-significant findings with interventions including resistance training, aerobic exercise, toileting behavior and biofeedback, pelvic floor exercises, patient education, swallowing rehabilitation, dietary instruction and training, manual therapy and upper extremity exercise. [150][151][152][153][154][155][156][157][158][159][160][161][162][163][164][165][166][167] .…”
Section: Activities Of Daily Living and Instrumental Activities Of Daily Living (Adl/iadl)mentioning
confidence: 99%
“…Eighteen ADL/IADL studies (31%) reported non-significant findings with interventions including resistance training, aerobic exercise, toileting behavior and biofeedback, pelvic floor exercises, patient education, swallowing rehabilitation, dietary instruction and training, manual therapy and upper extremity exercise. [150][151][152][153][154][155][156][157][158][159][160][161][162][163][164][165][166][167] .…”
Section: Activities Of Daily Living and Instrumental Activities Of Daily Living (Adl/iadl)mentioning
confidence: 99%
“…Several validated measures are available for the assessment of patient reported outcomes in lymphedema. Some tools, such as the Disabilities of Arm Shoulder and Hand questionnaire (DASH), are non-specific and measure the degree of disability resulting from functional changes in the upper extremity resulting from lymphedema [38,39]. Other outcome measures, such as the LLIS, lymphedema quality of life questionnaire (LYMQOL), or the ULL27, have been specifically developed to assess the degree of disability in various scales resulting from lymphedema [24,25,40].…”
Section: Promsmentioning
confidence: 99%
“…It is known that lymphedema is an important complication seen in many women after BCT [23]. Pasket and Stark, conducted a study about general information given to people diagnosed with cancer, treatment, and effects on participants that survive and reached the conclusion that the use of the affected arm after surgery increased lymphedema by 40% [24].…”
Section: Discussionmentioning
confidence: 99%
“…Breast cancer can lead to different losses of function due to radical surgical interventions and radiotherapy after treatment [23]. Loss of function may include pain limitations in the shoulder area, loss of muscle strength in the upper limb, and locomotor system disorders such as lymphedema and psychological and cosmetic problems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation